2003
DOI: 10.4049/jimmunol.171.7.3379
|View full text |Cite
|
Sign up to set email alerts
|

Electroporation Enables Plasmid Vaccines to Elicit CD8+ T Cell Responses in the Absence of CD4+ T Cells

Abstract: In vivo electroporation dramatically enhances plasmid vaccine efficacy. This enhancement can be attributed to increased plasmid delivery and, possibly, to some undefined adjuvant properties. Previous reports have demonstrated CD8+ T cell priming by plasmid vaccines is strongly dependent upon CD4+ T cell help. Indeed, the efficacy of a plasmid vaccine expressing Escherichia coli β-galactosidase was severely attenuated in MHC class II-deficient (C2D) mice. To determine whether electroporation could compensate fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
3

Year Published

2004
2004
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 42 publications
0
21
0
3
Order By: Relevance
“…injection of 10 7 PFU Vacc-ESOVA (a gift from J. Yewdell, National Institute of Allergy and Infectious Diseases, Bethesda, MD), which expresses an endoplasmic reticulum-targeted SIINFEKL epitope. Seven days later, virus replication was measured in the ovaries as described previously (33).…”
Section: Virus Challengementioning
confidence: 99%
“…injection of 10 7 PFU Vacc-ESOVA (a gift from J. Yewdell, National Institute of Allergy and Infectious Diseases, Bethesda, MD), which expresses an endoplasmic reticulum-targeted SIINFEKL epitope. Seven days later, virus replication was measured in the ovaries as described previously (33).…”
Section: Virus Challengementioning
confidence: 99%
“…Also, however, the induction of an inflammatory response, due to the physical stimulation of skin cells by EP, might be crucial for enhancing immune responses [80]. This undefined adjuvant effect might be possibly mediated through local minor tissue damage and release of inflammatory factors [79,81,82]. Recent data suggest that in addition to enhancing gene delivery, EP provides adjuvant-like effects [82,83].…”
Section: Discussionmentioning
confidence: 99%
“…This undefined adjuvant effect might be possibly mediated through local minor tissue damage and release of inflammatory factors [79,81,82]. Recent data suggest that in addition to enhancing gene delivery, EP provides adjuvant-like effects [82,83]. Several reports have shown that the local effect by EP is responsible for the generation of an inflammatory environment with immune cell infiltration.…”
Section: Discussionmentioning
confidence: 99%
“…Способ электропорации сделал возможным чрескожную доставку лекарств при воспалительных заболевани-ях [49]; обезболивании [50], химиотерапии опухо-лей [51][52][53][54][55][56][57]. Кроме того, электропорация расширяет возможности генной терапии, позволяющий введе-ние ДНК, генов в клетки [58,59], а также для вак-цин [60][61][62].…”
Section: электропорацияunclassified